Global burden of 87 risk factors in 204 countries and territories, 1990–2019 : a systematic analysis for the Global Burden of Disease Study 2019 - GBD 2019 Risk Factors Collaborators (2020)
Information about authors at https://doi.org/10.1016/S0140-6736(20)30752-2